1942
DOI: 10.1001/jama.1942.02830060001001
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Hemoglobin Regeneration in Blood Donors

Abstract: During the past twenty years there has been a great increase in the number of blood transfusions administered, and the recent use of normal and lyophilized serum in combating shock and in restoring the plasma proteins to their normal level promises to increase still further the already great demand for blood. In spite of the frequent use of whole blood and blood serum there have been surprisingly few studies on the rate of hemoglobin regeneration in the blood donors. Most of the recorded observations have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

1942
1942
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 4 publications
0
28
0
Order By: Relevance
“…1 In accordance with guidelines of regulatory agencies and to protect whole blood donors from developing ID and anemia, many blood establishments worldwide require a minimum interval of 56 days between 2 donations. 2,3 This interval is based on studies from the 1940s and 1950s, investigating recovery of (only) Hb, 4,5 but more recently, it was reported to be too short to prevent ID. 6,7 Because Hb falls short as a marker for nonanemic ID, 8,9 and to prevent blood donors from developing ID, there is a need for additional insights into the kinetics of red cell indices and iron parameters over time after blood donation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 In accordance with guidelines of regulatory agencies and to protect whole blood donors from developing ID and anemia, many blood establishments worldwide require a minimum interval of 56 days between 2 donations. 2,3 This interval is based on studies from the 1940s and 1950s, investigating recovery of (only) Hb, 4,5 but more recently, it was reported to be too short to prevent ID. 6,7 Because Hb falls short as a marker for nonanemic ID, 8,9 and to prevent blood donors from developing ID, there is a need for additional insights into the kinetics of red cell indices and iron parameters over time after blood donation.…”
mentioning
confidence: 99%
“…4,5 Recently, in the Recipient Epidemiology and Donor Evaluation Study-III (REDS-III) study involving fewer time points and iron parameters, investigators also observed a decrease of Hb and hepcidin and increase of reticulocyte count and EPO upon blood donation. 16 Moreover, and similar to our observations, they found that (1) absolute hepcidin levels decreased more in high ferritin donors, whereas EPO increased more in those with low ferritin, indicating that erythropoietic response to severe blood loss varies with baseline iron stores, and (2) recovery to baseline ferritin levels in high ferritin donors was less complete.…”
mentioning
confidence: 99%
“…Whereas the iron delivered from normal reticuloendothelial stores or orally administered iron is sufficient for a marrow production response of only two to three times normal, the increased iron supply from nonviable red cells, hemolysis, or iron dextran infusions permits marrow production to rise acutely to levels of four to eight times normal. INTRODUCTION Although erythropoiesis has been extensively studied in a wide spectrum of disease states (1)(2)(3)(4)(5)(6)(7), there have been very few studies of the characteristics of the normal marrow response to varying degrees of anemia (8)(9)(10)(11)(12)(13)(14)(15). The wide variation in the level of red cell production which occurs with different anemias has been considered to be a function of both the relative level of hematocrit depression and a variety of biochemical abnormalities and cofactor deficiencies which interfere with cell growth and maturation.…”
mentioning
confidence: 99%
“…The rate at which the hemoglobin concentration falls after bleeding is shown in Figure 1 ( 11), and by others who have worked on the same subject ). The purpose of the figure is to show that the post-operative fall in hemoglobin follows a smooth curve, and that it is virtually complete by the third post-operative day.…”
Section: Section Imentioning
confidence: 72%